2010
DOI: 10.1088/2040-8978/13/1/015602
|View full text |Cite
|
Sign up to set email alerts
|

Spectral characterization of two-dimensional Thue–Morse quasicrystals realized with high resolution lithography

Abstract: One-dimensional Thue-Morse (ThMo) lattices are examples of self-similar structures that exhibit bandgap phenomena. ThMo multilayers may also possess fractal photonic bandgaps that give rise to large omnidirectional reflectance and light emission enhancement effects. Two-dimensional (2D) ThMo aperiodic quasicrystals possess interesting properties for photonic applications too. Here we demonstrate the experimental fabrication of large area 2D ThMo lattices into polymeric substrates at nanometer scale by electron… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…Optical and plasmonic behaviors of the ThMo patterns have been widely reported in literature from both numerical and experimental point of views. They make such geometry an attractive candidate for the realization of high-performance nanosensors [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Optical and plasmonic behaviors of the ThMo patterns have been widely reported in literature from both numerical and experimental point of views. They make such geometry an attractive candidate for the realization of high-performance nanosensors [21][22][23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, novel PBG aperiodic structures defined by recursive substitutional sequences like one-dimensional (1D) and 2D Thue-Morse patterns cannot be realized even in principle by multiple-beam interference. Experimental realization of photonic structures exhibiting large area 2D Thue-Morse arrangement has been recently reported by the authors for the first time to our knowledge [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…ThMo aperiodic geometry is generated by the iterative substitution rule: A → AB, B → BA that can be extended to two dimensions [ 29 ]. Optical properties of the ThMo nanopattern have been widely investigated and their peculiarities (singular continuous Fourier/Diffraction spectra, self-similar hierarchy of pseudoband-gap regions, omnidirectional reflectivity, and light emission enhancement) make such geometries attractive candidates for the realization of high-performance plasmonic nanosensors [ 23 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. Despite the greater difficulty of both design and fabrication that they require compared to conventional periodical pattern, aperiodic arrangements show important advantages for the realization of sensing systems.…”
mentioning
confidence: 99%
“…In order to obtain an optical sensor suitable for the pathogen detection, we chose to exploit as metastructure the ThMo distribution, whose potential for sensing was already demonstrated [ 23 , 36 , 39 ]. In our previous work, we studied the plasmonic properties of ThMo-arranged NCs by Finite Difference in Time Domain (FDTD) simulations suggesting a characteristic near-field with a high spatial density of hot-spots [ 31 ]. Moreover, we demonstrated that a sensor patterned with such geometry and functionalized with 4-ATP significantly enhanced the whole spectrum of a model protein (Bovine Serum Albumin—BSA) [ 39 ].…”
mentioning
confidence: 99%